Peningkatan Proses Hasil Belajar Menggunakan PBL Pembelajaran IPAS Kelas IV SDN 031/VI Rantau Panjang - Winda Winda; Sundahry Sundahry; Nurlev Avana (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research was driven by Improving the Learning Process and Outcomes Using the Problem-Based Learning Model in Science and Social Studies (IPAS) for Grade IV Students at SDN 031/VI Rantau Panjang.The purpose of the study was to explore how the application of the Problem Based Learning (PBL) model could enhance the learning process and outcomes. The study utilized a Classroom Action Research (CAR) approach, implemented over two cycles, each comprising planning, action, observation, and reflection phases. The participants were 20 fourth-grade students. Data were gathered through observation, tests of learning outcomes, and documentation, then analyzed using both qualitative and quantitative methods. The results demonstrated marked improvements in teaching effectiveness and student performance. In the first cycle, teacher activity averaged 69.04%, increasing to 83.33% in the second cycle. Student participation improved from 60% to 85%. Similarly, learning mastery rose from 64.75% in the initial cycle to 81.25% in the subsequent one. These findings suggest that the PBL model significantly contributes to enhancing student engagement and comprehension of IPAS content. Therefore, this model is recommended as an effective instructional strategy that promotes active, student-centered, and meaningful learning.